Analysis of subcarrier multiplexing signals in optical fibre communication - Cheng, Linghao (2008)
This thesis aims to provide a comprehensive analysis of the nonlinear distortion in SCM optical communication systems. After the basic introduction to subcarrier multiplexed optical communication systems, the three most significant types of nonlinear distortions are analyzed. For each type of nonlinear distortion, an analytical model is presented and verified by numerical simulations and experiments. These analytical models result in many new closed-form expressions. Therefore, the analytical models enable one to get a better physical insight into the nonlinear distortion phenomena and help one to evaluate the impact of these distortions quickly. Hence, these analytical models can facilitate the task of system design greatly. The thesis concludes by mentioning the major conclusions and achievements of the work presented here and the proposed future work.